2017
DOI: 10.1002/adma.201702350
|View full text |Cite
|
Sign up to set email alerts
|

Chloride Passivation of ZnO Electrodes Improves Charge Extraction in Colloidal Quantum Dot Photovoltaics

Abstract: The tunable bandgap of colloidal quantum dots (CQDs) makes them an attractive material for photovoltaics (PV). The best present-day CQD PV devices employ zinc oxide (ZnO) as an electron transport layer; however, it is found herein that ZnO's surface defect sites and unfavorable electrical band alignment prevent devices from realizing their full potential. Here, chloride (Cl)-passivated ZnO generated from a solution of presynthesized ZnO nanoparticles treated using an organic-solvent-soluble Cl salt is reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
128
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(138 citation statements)
references
References 48 publications
9
128
0
1
Order By: Relevance
“…The complete disappearance of N can be attributed to the thermal decomposition of NH 4 Cl and release of NH 3 . The incorporation of Cl is related to the rich oxygen vacancy defects on the ZnO surface . The Cl atoms fill into the surface lattice and form Zn–Cl bonds, which is consistent with the peaks of Cl 2p and the shift of Zn 2p toward high energy direction for the ZnO–Cl layer.…”
Section: Resultssupporting
confidence: 72%
“…The complete disappearance of N can be attributed to the thermal decomposition of NH 4 Cl and release of NH 3 . The incorporation of Cl is related to the rich oxygen vacancy defects on the ZnO surface . The Cl atoms fill into the surface lattice and form Zn–Cl bonds, which is consistent with the peaks of Cl 2p and the shift of Zn 2p toward high energy direction for the ZnO–Cl layer.…”
Section: Resultssupporting
confidence: 72%
“…Introduction Semiconductor quantum dots (QDs) are emerging as competitive candidates for optoelectronic devices owing to their tunable bandgaps, high absorption coefficients, easy solution processabilities, and superior ambient stabilities . Particularly, lead sulfide (PbS) QDs have been widely applied in photovoltaic field . Great progress has been made in modifying the surface of PbS QDs with ligands (from oleic acid to the halides or chalcogenides), which efficiently optimized the light absorption and carrier transport properties of the PbS QDs film.…”
Section: Average Values and Standard Deviations From The 20 Devices Fmentioning
confidence: 99%
“…[4,6,14] To improve interfacial electron transfer, metal oxide based ETLs have been continuously developed through defect density reduction and/or energy level matching. are employed as ETLs, iodide-doped PbS-CQD films as photon absorbing active layers, and thiol-passivated p-type CQD (p-CQD) as HTLs.…”
mentioning
confidence: 99%
“…are employed as ETLs, iodide-doped PbS-CQD films as photon absorbing active layers, and thiol-passivated p-type CQD (p-CQD) as HTLs. [4,6,14] Despite the superior properties of the p-CQDs, the requirement of an intricate solid-state-ligand-exchange (SSE) step induces high material consumption and hampers high-throughput production. [7,8,[15][16][17] While the engineering of ETLs has been widely studied, few studies on HTL materials have been reported because of the dominant performance of the thiol-passivated p-CQDs.…”
mentioning
confidence: 99%